2016
DOI: 10.1515/biol-2016-0055
|View full text |Cite
|
Sign up to set email alerts
|

Remediation of deltamethrin contaminated cotton fields: residual and adsorption assessment

Abstract: Pakistan occupies a significant global position in the growing of high quality cotton. The extensive application of pesticides on agricultural products leads to environmental risk due to toxic residues in air, water and soil. This study examined the chemodynamic effect of Deltamethrin on cotton fields. Samples were collected from the cotton fields of D.G. Khan, Pakistan and analyzed for heavy metal speciation patterns. Batch experiments were administered in order to study the adsorption of Deltamethrin in cott… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…Briefly, available data from our analyses have revealed that sewage and industrial wastewater is unfit for irrigation purpose and has potential hazards due to the accumulation of metals. Earlier studies by Rafique et al (2016) and Latif et al (2018) also supported the findings of the present investigation and confirmed the availability of different heavy metals in cultivated soil of various areas of the Dera Ghazi Khan district. These areas were irrigated with sewage and industrial wastewater for a long time.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Briefly, available data from our analyses have revealed that sewage and industrial wastewater is unfit for irrigation purpose and has potential hazards due to the accumulation of metals. Earlier studies by Rafique et al (2016) and Latif et al (2018) also supported the findings of the present investigation and confirmed the availability of different heavy metals in cultivated soil of various areas of the Dera Ghazi Khan district. These areas were irrigated with sewage and industrial wastewater for a long time.…”
Section: Discussionsupporting
confidence: 91%
“…Likewise, the mean accumulation of heavy metals for all 17 stands has also revealed an elevated concentration of chromium (11.32 mg/ kg). Foregoing deep insight, by differentiating the irrigated sites, ten sites SF-5, SF 7-10, and SF 12-17 have been found with the elevated metal contents (Cr, Cu, Ni, Pb, and Zn) under the cultivation of the cotton crop, might be due to excessive use of fertilizers and pesticides along with the wastewater application as reported earlier (Rafique et al, 2016;Gill et al, 2016;Gill et al, 2017). Briefly, available data from our analyses have revealed that sewage and industrial wastewater is unfit for irrigation purpose and has potential hazards due to the accumulation of metals.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Ozone gas (O 3 ) was used to remove leftover deltamethrin, which was utilized as an insecticide in the treatment of wheat crops ( Triticumaestivum L.) [ 8 ]. Additionally, soil is a very effective degrading agent for deltamethrin elimination (95 percent in 54 min at pH 10) in cotton field water [ 9 ]. Deltamethrin was removed (88.3 and 82.8 percent, respectively) by degrading its residuals using two Serratiamarcescens (DeI-1 and DeI-2, respectively) bacterial strains [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Literature showed that the pollution load from tanning industries in cities like Sialkot, Kasur and Faisalabad were very high 13,14 . The damage to the environment by the hazardous tannery effluents is becoming an acute problem in the country.…”
mentioning
confidence: 99%